DEVELOPMENT AND VALIDATION OF A HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY WITH PHOTODIODE ARRAY DETECTION (HPLC-PDA) BIOANALYTICAL METHOD FOR QUANTIFICATION OF IMATINIB MESYLATE IN HUMAN PLASMA - BATCHA, JAYA SHREE DILLI; GUPTA, ASHUTOSH; MOORKOTH, SUDHEER; MALLAYASAMY, SURULIVELRAJAN (International Journal of Applied Pharmaceutics, 2025)
Objective: Chronic Myeloid Leukemia (CML) is a myeloproliferative neoplasm represented by the uncontrolled growth of myeloid cells at different stages of maturation. Imatinib Mesylate (IM) has set a new standard for treating CML and other cancers. Therefore, in order to do PK investigations and to periodically monitor imatinib, clinical laboratories need an analytical approach that is practically adaptable. The current analytical techniques for use laborious, time-consuming. The aim of this study was to develop and validate a fast and simple method for imatinib quantification in human plasma using High-Performance Liquid Chromatography (HPLC) using photodiode array detection. Methods: A mobile phase comprising potassium dihydrogen phosphate, methanol, and acetonitrile (30:35:35) with isocreatic programming was utilized to achieve the separation on an ODS C18 column (150×4.6 mm), 4µm column. The procedure consisted of simple protein precipitation with cold methanol extraction to obtain the maximum recovery from a 90 μl plasma sample. Results: The regression coefficient of 0.99 indicates that the procedure is linear in the range of 100 to 10,000 ng/ml. The total recovery of the approach under lower quality control was 102.45%, at middle-quality control 101.70%; and at higher quality control, it was 95.75%. Both accuracy and precision were within acceptable bounds. Conclusion: The quantification of imatinib levels in plasma of CML patients for Pharmacokinetic (PK) assessments and Therapeutic Drug Monitoring (TDM) necessitates the development and validation of an easy-to-use, effective, repeatable, and environmentally friendly analytical technique.